Reproductive constraints and the evolution of life histories with indeterminate growth - Charnov, Eric L. (The National Academy of Sciences, 2001)
A prominent feature of comparative life histories in fish (and other indeterminate growers) is the approximate invariance across species of certain dimensionless numbers made up from reproductive and timing variables. The two best known are the age at maturity (α) divided by the average adult lifespan (E), and the proportion of a body mass given to reproduction per year (c) multiplied by E. This article uses evolutionary life-history theory for nongrowing populations to predict the numeric value of these numbers for fish and lizards, with several new implications for the dynamics of ontogenetic development.